Pengaruh Menonton VCD Tentang Cidera Kepala Terhadap Kepatuhan Menggunakan Helm Siswa SMK Pengendara Sepeda Motor Di Kota Surakarta - Suyanto Suyanto; Hartono Hartono ((JKG) Jurnal Keperawatan Global, 2019)
Background: Various efforts have been made to reduce the risk of head injury due to motorcycle accident. But the effort has not succeeded that looks still high head injury rate so that it enters in 10 diseases most in Surakarta. Police records, motorcycle accidents in the Surakarta region ranks the highest compared to five other Central Java areas which tend to increase. An effort to reduce the risk of head injury is to increase knowledge about head injury. Especially in the vocational school students who use motorcycles for their groups at high risk of accidents and head injuries. The study wanted to see the effect of watching videos on knowledge and compliance using helmets of motorcycling students in Surakarta. Method: The design of this study was quasi experiment using pre-post test approach on population of vocational students in Surakarta with 343 samples using a knowledge questionnaire observation and compliance observation sheets using a helmet. Research data were analyzed using Chi Square Test. Result: The results showed that there was a significant difference in knowledge of vocational students about head injuries before and after watching video. As for the helmet there are significant differences. Conclusion: Researchers suggest student knowledge about head injury and compliance using a helmet.